2018
DOI: 10.1557/adv.2018.414
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ar Implantation on the Precipitation in Au Ion Irradiated AISI 316L Solution Annealed Alloy

Abstract: ABSTRACT200 μm thick solution annealed AISI 316L stainless steel foils were implanted with Ar ions to produce a 0.25 at. % concentration-depth plateau extending from the near surface to a depth of ≈ 250 nm, and then annealed at 550°C for 2 hours to form small Ar bubbles and Ar-vacancy clusters. Distinct sets of samples (including control ones without Ar) were irradiated at the temperature of 550 °C with Au ions accelerated at 5 MeV to produce an average damage content about ≈36 dpa at the region containing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…[ 50 ] Although such retardation has been similarly reported in age‐hardenable Fe‐C alloys, [ 59,60 ] this phenomenon is opposed to common reports on austenitic stainless steels under energetic irradiation environments. [ 61–64 ] Recent values of solute‐vacancy binding energies were calculated by Wolverton; [ 65 ] ii)Guinier‐Preston zones (GPZs) and precipitation kinetics acceleration: as a result of neutron‐induced activation and transmutation of 27 AI, 28 Si via the nuclear reaction shown in Equation (), [ 66 ] increased nucleation and growth rates of GPZs and precipitation of phases such as Mg2Si were observed in commercial AlMg and AlMgSi alloys at temperatures where vacancies are mobile. [ 50,53 ] Acceleration of θ‐phase (Al2Cu) precipitation in Al‐based Cu containing alloys was also reported under low temperature neutron irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…[ 50 ] Although such retardation has been similarly reported in age‐hardenable Fe‐C alloys, [ 59,60 ] this phenomenon is opposed to common reports on austenitic stainless steels under energetic irradiation environments. [ 61–64 ] Recent values of solute‐vacancy binding energies were calculated by Wolverton; [ 65 ] ii)Guinier‐Preston zones (GPZs) and precipitation kinetics acceleration: as a result of neutron‐induced activation and transmutation of 27 AI, 28 Si via the nuclear reaction shown in Equation (), [ 66 ] increased nucleation and growth rates of GPZs and precipitation of phases such as Mg2Si were observed in commercial AlMg and AlMgSi alloys at temperatures where vacancies are mobile. [ 50,53 ] Acceleration of θ‐phase (Al2Cu) precipitation in Al‐based Cu containing alloys was also reported under low temperature neutron irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…They have also been considered as structural components in innovative nuclear fusion test reactors due to the very good results they have obtained in applications in extreme environments [ 117 , 118 , 119 ]. The 300 series steels (Fe-Cr-Ni alloy) have good corrosion and mechanical properties for applications at high temperatures, making them viable to be applied in aeroengine parts, turbochargers, oil and gas pipelines [ 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 ], and as structural components in nuclear reactors [ 116 , 117 , 132 , 133 ]. The 304 SS is one of the austenitic steels that is most used in nuclear reactors.…”
Section: Relations Between Microstructures and Alloys Performance Of ...mentioning
confidence: 99%
“…A recent research study showed that for AISI 316L samples previously implanted with Ar and irradiated with 5 MeV Au ions a change in the irradiation temperature can induce the formation and evolution of radiation-induced precipitates, which was not observed in the samples without the previous Ar implantation. It was shown that the formation of RIP is highly dependent on the previous concentration of vacancies [15]. Also, by changing the ion from Au to Ag and subjecting the AISI 316L samples to the same total amount of damage and temperature results in a change in the microstructure due to the larger production of vacancies in the denser collision cascades of Au [16].…”
Section: Introductionmentioning
confidence: 99%